Persepsi Mahasiswa PGSD pada Inovasi Pembelajaran Berbasis E-Learning - Khusniyah, Tri Wardati; Wana, Prima Rias (Universitas Negeri Malang, 2020)
This study was aimed at describing the perceptions of students in e-learning based learning in the elementary school teacher education study programs STKIP Modern Ngawi. Students' perceptions that were explored included aspects of student knowledge on e-learning based learning, e-learning as teaching material, readiness of human resources, e-learning ease, usefulness of e-learning, and obstacles during the course of e-learning based learning. The research subjects were first semester students of the elementary school teacher education study programs STKIP Modern. Data collection was done by questionnaire and observation. Data were analyzed using qualitative descriptive techniques. The results show that students already know the term e-learning based learning, e-learning is an effective and efficient teaching material, e-learning facilitates learning, e-learning provides benefits to the quality of student learning, and an increase in e-learning is needed in STKIP Modern Ngawi.Â Penelitian ini bertujuan mendeskripsikan persepsi-persepsi mahasiswa pada pembelajaran berbasis e-learning di program studi PGSD STKIP Modern Ngawi. Persepsi-persepsi mahasiswa yang digali meliputi aspek pengetahuan mahasiswa pada pembelajaran berbasis e-learning, e-learning sebagai bahan ajar, kesiapan sumber daya manusia, kemudahan e-learning, kebermanfaatan e-learning, dan kendala selama berlangsungnya pembelajaran berbasis e-learning. Subyek penelitian adalah mahasiswa semester 1 program studi PGSD STKIP Modern Ngawi. Pengumpulan data dilakukan dengan angket dan pengamatan. Data dianalisis dengan teknik deskriptif kualitatif. Hasil penelitian menunjukkan bahwa mahasiswa telah mengetahui istilah pembelajaran berbasis e-learning, e-learning merupakan bahan ajar yang efektif dan efisien, e-learning memudahkan pembelajaran, e-learning memberikan manfaat pada kualitas belajar mahasiswa, dan diperlukan adanya peningkatan pada e-learning di STKIP Modern Ngawi.